(untitled) (Bangladesh Critical Care Journal, 2024)
Fascioliasis is an infection caused by a trematode of the liver, Fasciola hepatica, which affects sheep, goats and cattle. Humans become accidental hosts through drinking contaminated water or ingesting raw green vegetables that has been contaminated with encysted metacercariae, which is the infective form. Fascioliasis has a hepatic phase and a biliary phase, each displaying different clinical signs and symptoms. Common signs and symptoms of the hepatic phase are abdominal pain, fever, eosinophilia, and abnormal liver function tests. The biliary phase of the disease usually presents with intermittent right upper quadrant pain with or without cholangitis or cholestasis. However, it is very rare to find a living flukes in the common bile duct (CBD) and duodenal lumen as it usually lives in gall-bladder and smaller biliary tracts. Here we report a case of human infestation of Fasciola hepatica, who presented with respiratory tract infection with abdominal pain & dyspeptic symptoms and eventually during evaluation, an upper gastro-intestinal endoscopy revealed several flat worms at the second part of the duodenum. The worms were sent to microbiology department for identification. The organisms were confirmed to be Fasciola hepatica. The patient was given tablet Nitazoxanide 500mg 12 hourly for 7 days. The symptoms reduced in intensity after two days of nitazoxanide. The patient was then discharged with an advice of a stool routine examination after one month of completion of nitazoxanide. As fasciolosis is non endemic in our country, a high degree of suspicion is required to ensure early detection and management of such cases. Patients with abdominal pain, altered liver function tests & eosinophilia should always be evaluated for a suspected Fasciola hepatica infection and should be kept as a differential in these cases. Bangladesh Crit Care J March 2024; 12 (1): 54-57